Changes in exercise performance and hormonal concentrations over a big ten soccer season in starters and nonstarters - Kraemer, W. J.; French, D. N.; Paxton, N. J.; Häkkinen, K.; Volek, J. S.; Sebastianelli, W. J.; Putukian, M.; Newton, R. U.; Rubin, M. R.; Gomez, A. L.; Vescovi, J. D.; Ratamess, N. A.; et al. (The Journal of Strength and Conditioning Research, 2004)
As a consequence of the physiological demands experienced during a competitive soccer season, the antagonistic relationship between anabolic and catabolic processes can affect performance. Twenty-five male collegiate soccer players were studied throughout a season (11 weeks) to investigate the effects of long-term training and competition. Subjects were grouped as starters (S; n = 11) and nonstarters (NS; n = 14). Measures of physical performance, body composition, and hormonal concentrations (testosterone [T] and cortisol [C]) were assessed preseason (T1) and 5 times throughout the season (T2-T6). Starters and NS participated in 83.06% and 16.95% of total game time, respectively. Nonstarters had a significant increase (+1.6%) in body fat at T6 compared to T1. Isokinetic strength of the knee extensors (1.05 rad·sec-1) significantly decreased in both S (-12%) and NS (-10%; p 0.05) at T6. Significant decrements in sprint speed (+4.3%) and vertical jump (-13.8%) were found at T5 in S only. Though within normal ranges (10.4-41.6 nmol·L-1), concentrations of T at T1 were low for both groups, but increased significantly by T6. Concentrations of C were elevated in both groups, with concentrations at the high end of the normal range (normal range 138-635 nmol·L-1) at T1 and T4 in NS and T4 in S, with both groups remaining elevated at T6. Data indicate that players entering the season with low circulating concentrations of T and elevated levels of C can experience reductions in performance during a season, with performance decrements exacerbated in starters over nonstarters. Soccer players should therefore have a planned program of conditioning that does not result in an acute overtraining phenomenon prior to preseason (e.g., young players trying to get in shape quickly in the 6 to 8 weeks in the summer prior to reporting for preseason camp). The detrimental effects of inappropriate training do not appear to be unloaded during the season and catabolic activities can predominate.